An astronomically calibrated stratigraphy of the Mesoproterozoic Hongshuizhuang Formation, North China: Implications for pre-Phanerozoic changes in Milankovitch orbital parameters. (1st September 2020) - Cheng, Dawei; Zhang, Shuichang; Zhang, Zhijie; Zhou, Chuanmin; Wang, Huajian; Yuan, Xuanjun; Chen, Xingyu
Graphical abstract: Highlights: Multiple proxy series were used to identify the Milankovitch signals recorded in the Meso-proterozoic Hongshuizhuang Formation. All Milankovitch astronomical parameters were identified and their changes in Pre-Phanerozoic were assessed. This study emphasized the necessity of utilization of multiple paleoclimate proxies in cyclostratigraphy analysis. Abstract: This study presents a cyclostratigraphic investigation of the Mesoproterozoic Hongshuizhuang formation (about 1.45 Ga) in North China. High-resolution, continuous magnetic susceptibility and X-ray fluorescence elemental data were obtained from the YuanJi-2 drillcore. We tested the present astronomical age models using the multi-taper spectral analysis and correlation coefficient (COCO) methods from three paleoclimate proxies, i.e. magnetic susceptibility, Al and Ca elemental contents. The proxies record orbital forcing cyclicity with varying sensitivities which was attributed to their distinctive corresponded to depositional environments or diagenesis. The 405-kyr-calibrated ATS indicates the HSZ Formation has a ~3.1 Myr duration and an average sedimentation rate of ~3.94 cm/kyr. According to our results, the eccentricity at 1.45 Ga has cycle periods of ~405, ~125, ~115 and ~90 kyr. In addition, several significant cycle periods at ~28–20 kyr, ~18.2 kyr and ~16.3–14 kyr are regarded as the obliquity or precession cycles.